The effect of perceived nostalgia on place attachment - Mohsen Akbari (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2020)
Background and Purpose of Research: Today, consumer emotional arousal has become very popular among marketers. It is widely accepted that people’s old memories can serve as an excellent tool to sell products to them. Advertising experts have always tried to tie their products to the memories of simple and relaxing days of people. The places and their advertisement are not an exception. The importance of creating and maintaining a distinct environment is growing among tourism researchers and managers and is considered as a key factor in attracting and satisfying customers as well as increasing financial performance by maximizing revenue and market share in the tourism industry. Therefore, this paper aims to investigate the effect of perceived nostalgia on place attachment. Research method: in terms of purpose this research is applied and in terms of method it is descriptive-survey. A questionnaire was used for data collection in which 302 customers of “Sini Por” traditional restaurant were analyzed using structural equations technique and Smart PLS software.